Relating solvatochromism and solvatomorphism in organic dyes using high pressure - Elena Boldyreva (IUCrJ, 2024)
By using complementary experimental methods including in situ high-pressure single-crystal X-ray diffraction and UV–Vis spectroscopy, the intricate connection between solvatochromism and solvatomorphism has been elucidated in a recent publication [Sobczak & Katrusiak (2024). IUCrJ, 11, 528–537]. The connection was demonstrated for an important pigment – Reichardt's dye – with potential applications in nonlinear optoelectronics and molecular pressure sensor development.